Designing a mosque charity box with voice recognition and GPS based on the internet of things - Ainun Azizah; Masthura Masthura; Mulkan Iskandar Nasution (Universitas Riau, 2024)
A security system for mosque donation boxes has been designed and built with the goal of developing a tool that can identify mosque charity box theft using the Internet of Things. The ATmega328P and ESP-32 microcontrollers are the two used in this device. Additionally, a GPS module, speech recognition, and an HC-SR04 ultrasonic sensor are included with this tool. This demonstrated that the Neo-6M GPS Module was used quite accurately with a distance difference of about 3 m. The test results from the GPS on the mosque's donation box obtained latitude and longitude points of 3.492006 and 98.587856, respectively, while the coordinate points on Google Maps were 3.491760 and 98.587943. The HC-SR04 ultrasonic sensor's purpose is to track movement in the Afterwards, a buzzer or early-warning alarm will ring, and Wi-Fi will notify the telegram application of the coordinates. This tool also includes a pretty contemporary voice recognition-based system for opening and closing donation boxes, which can accurately record, recognize, and detect sound.